THE EFFECT OF PLYOMETRIC EXERCISES BY ADDING WEIGHTS TO BODY WEIGHT TO DEVELOP PERFORMANCE AND SOME PHYSIOLOGICAL INDICATORS FOR WEIGHTLIFTERS UNDER 20 YEARS OF AGE - Abdal Redha, Ammar Hasan; Eesee Kadhim, Abdullah; Riyadh Ahmed, Nabaa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The weight-pushing competition is based on maximum strength, as well as explosive ability, correct technical performance, and digital achievement. Explosive ability depends primarily on maximum muscular strength, which is one of the important basic components for players in the weight-pushing competition. There have been recent changes in the training process for the weight-pushing competition, especially with regard to developing the explosive ability of players. One of the most recent of these exercises is plyometric exercises. The researcher chose an important training method for plyometric exercises, which is adding additional weight to the body weight of the weight-pushing player. Hence the importance of the current research because these exercises are different and varied within the exercises used by the coaches for this competition, and the training unit is for weightlifters under 20 years of age to develop their muscular strength and speed of performance, which is of very great importance in their digital achievement, and through the physiological indicator from the device Muscle and nerve EMG mapping in order to improve their physical and functional capabilities and develop the completion of this competition in a scientifically correct and standardized manner. The study aimed to identify plyometric exercises by adding weight to the athlete's body weight, as well as to know the difference between cardiac and post-tests for the functional and physical research variables, and also to know the impact that these exercises had on developing digital achievement and the physiological index. The researchers used the experimental method to suit the nature of the problem posed by the researchers. The research population was 15 players from the Central Euphrates national team for the weight-pushing competition, and the research sample was only 8 players.